2019
DOI: 10.3390/nu11123034
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences of Vitamin D Status across BMI Classes: An Observational Prospective Cohort Study

Abstract: Growing evidence reported that vitamin D deficiency is a common finding in obesity. Vitamin D status also seems to be sex-related, although little is known regarding this association. Therefore, the aim of this study was to investigate the sex-related differences of serum 25OH vitamin D (25OHD) concentrations across body mass index (BMI) classes and, if there were any differences, whether they could be explained by sex-related differences in body composition. We enrolled 500 subjects (250 males, age 37.4 ± 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
72
6
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 41 publications
13
72
6
3
Order By: Relevance
“…The serum levels of 25OHD were quantified by a direct competitive chemiluminescence immunoassay (CLIA) (Liaison, DiaSorin, Saluggia, Italy), with a specificity of 100% for 25OHD. The analytical measurement range of detection was 4-150 ng/mL, whereas the intra-assay CVs were 5%, 3%, and 5%, and the inter-assay CVs were 10%, 5%, and 8% for low, medium, and high points of the standard curve, respectively (as previously reported in [53][54][55][56]). The vitamin D deficiency was defined as 25OHD levels < 20 ng/mL (50 nmol/L), vitamin D insufficiency as 25OHD levels between 21 and 29 ng/mL (from 53 to 73 nmol/L) and vitamin D sufficiency as 25OHD levels ≥30 ng/mL (75 nmol/L) [57].…”
Section: Assay Methodssupporting
confidence: 59%
“…The serum levels of 25OHD were quantified by a direct competitive chemiluminescence immunoassay (CLIA) (Liaison, DiaSorin, Saluggia, Italy), with a specificity of 100% for 25OHD. The analytical measurement range of detection was 4-150 ng/mL, whereas the intra-assay CVs were 5%, 3%, and 5%, and the inter-assay CVs were 10%, 5%, and 8% for low, medium, and high points of the standard curve, respectively (as previously reported in [53][54][55][56]). The vitamin D deficiency was defined as 25OHD levels < 20 ng/mL (50 nmol/L), vitamin D insufficiency as 25OHD levels between 21 and 29 ng/mL (from 53 to 73 nmol/L) and vitamin D sufficiency as 25OHD levels ≥30 ng/mL (75 nmol/L) [57].…”
Section: Assay Methodssupporting
confidence: 59%
“…Finally the house con nement imposed by quarantine could be associated to the decreased intake of fresh food, as fruit, vegetables and sh, all food rich in vitamins (including vitamin C, beta-carotene, and vitamin D), minerals (including selenium and zinc) and omega 3 fatty acids with anti-in ammatory and antioxidants activities. The low consumption of these micronutrients is associated with both obesity and sleep disturbance [54][55][56]; in particular, vitamin D plays a key role in the relationship between obesity and sleep disturbances [57][58][59][60].…”
Section: Sleep Qualitymentioning
confidence: 99%
“…On the other hand, sex may influence on the level of vitamin D. Muscogiuri et al found that 25OHD concentration was higher in males compared with females in all BMI groups. Males with vitamin D deficiency had lower fat mass compared with females [42].…”
Section: Discussionmentioning
confidence: 90%